Molecular and serological data supporting the role of Q fever in abortions of sheep and goats in northern Egypt. (December 2018) - Selim, Abdelfattah; Ali, Abdel-Fattah; Moustafa, Samar M.; Ramadan, Eman
Abstract: Q fever is a worldwide zoonotic disease, caused by Coxiella burnetii ( C. burnetii ), an obligate intracellular bacterium. The epidemiological data about the Q fever situation in Egypt is limited. The present study investigated the seroprevalence of Q fever among small ruminants in some localities in the northern Egypt and reported the shedders using specific real-time PCR (Rt-PCR). A total of 190 sera and vaginal swabs (110 sheep and 80 goats) were collected from aborted cases. Indirect ELISA was used to detect specific antibodies against C. burnetii, and Rt-PCR was used to detect DNA in the shedder animals. The study revealed that infection was significantly higher in sheep (22.7%) than in goats (12.5%) ( p < 0.05). The Menoufia and Gharbia governorates had 20% seropositive animals while Qalubia and Alexandria had 15% and 17.5% seropositive animals, respectively. Using a Rt - PCR assay, C. burnetii was detected in 33.6% and 16.3% of sheep and goats, respectively. The findings of the study demonstrate that Q fever may be enzootic among small ruminants and distributed in the northern Egyptian Governorates. Further studies are needed in different regions to gain better understanding of the epidemiology of Q fever all over the country and to develop an appropriate preventive strategy for human and animals. Highlights: Q fever is an important cause for abortion in sheep and goats. Serological and molecular detection of C. burnetii among sheep and goats. Q fever distributed in different localities in Egypt and have risk importance to human.